Pemikiran Monzer Kahf Tentang Epistimologi Rasionalitas Ekonomi Islam - Zainuri, Mohammad; Al-Mansury, Abdul Hamid (LP2M IAI Miftahul Ulum Pamekasan, 2024)
Epistemology is a branch of philosophy that discusses a theory of knowledge (the body of knowledge). However, we cannot be sure that this knowledge is correct even though it is compiled and selected based on epistemological considerations. This is because there is no guarantee for knowledge which is only considered as an analysis of the possibilities that become the basis for carrying out an action through the rational aspect. In economic activities, the problem faced by Islamic economics is the gap between ideal behavior or what should be done and real behavior that occurs because it is not in accordance with what should be done. Moreover, with the development of an increasingly modern era, there is a need for the thinking of contemporary Muslim economists, one of whom is Monzer Kahf, whom we can relate to the epistemology of Islamic economics and its rationality. The purpose of this research is to find out from existing Islamic economics whether it is in accordance with the events or activities in the field accompanied by their respective rationalities. So, with monzer kahf's thoughts on Islamic Economics can be analyzed in theoretical and practical terms. Based on the results of this study, it shows that there are several thoughts from figures from Monzer Kahf that we analyze so that we can find out about theories that are epistemologically examined with the rationality aspects of existing Islamic Economics. Keywords: Epistemology, Islamic Economic Rationality, Monzer Kahf